Pengaruh Kompetensi dan Kecerdasan Emosional terhadap Produktivitas Kerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Pegawai Sekretariat Daerah Kota Solok - Fitra, Prisda; Elfiswandi, Elfiswandi; Lusiana , Lusiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the effect of competence and emotional intelligence on employee work productivity with work motivation as an intervening variable on Solok City Regional Secretariat Employees. The method used is multiple linear regression analysis and path analysis, by distributing 97 questionnaires. The results of the study There is a positive and significant effect of competence on work motivation at the Solok City Regional Secretariat. There is a positive and significant effect of emotional intelligence on work motivation at the Solok City Regional Secretariat. There is a positive and significant effect of competence on work productivity at the Solok City Regional Secretariat. There is a positive and significant effect of emotional intelligence on work productivity at the Solok City Regional Secretariat. There is a positive and significant effect of work motivation on work productivity at the Solok City Regional Secretariat. Work motivation is able to mediate the effect of competence on work productivity at the Solok City Regional Secretariat. Work motivation is able to mediate the effect of emotional intelligence on work productivity at the Solok City Regional Secretariat. Finally, the author suggests to the Regional Secretariat of Solok City to further improve the emotional intelligence of employees because it has the most dominant value of influence on work productivity at the Regional Secretariat of Solok City